Enhancing EFL Students’ Writing Ability Through Clustering Technique in Hortatory Exposition Texts - Charissa Wahyu Qomala Rahma; Kristi Nuraini; Widya Oktarini; Siti Nuryati (South Sulawesi Education Development (SSED), 2026)
This study explores the effectiveness of the clustering technique in enhancing students’ writing performance in composing hortatory exposition texts. Conducted as Classroom Action Research (CAR) over two cycles, the research involved 15 twelfth-grade students at SMA Muhammadiyah 1 Rambipuji during the 2024-2025 academic year. Qualitative and quantitative data were gathered through writing assessments and an observation checklist. In the first cycle, students exhibited limited engagement, weak organization of ideas, and low confidence. After pedagogical refinements in the second cycle – such as guided modeling, collaborative tasks, and structure scaffolding – students showed marked improvement in motivation and writing quality. Their text reflected better organization, more persuasive content, and improved grammar and vocabulary. Clustering helped the student visualize engagement. The findings suggest that clustering is an effective and practical pre-writing strategy for improving argumentative writing skills in EFL contexts.